The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1088/2041-8205/797/2/l19
|View full text |Cite
|
Sign up to set email alerts
|

The Turbulent Dynamo in Highly Compressible Supersonic Plasmas

Abstract: The turbulent dynamo may explain the origin of cosmic magnetism. While the exponential amplification of magnetic fields has been studied for incompressible gases, little is known about dynamo action in highly compressible, supersonic plasmas, such as the interstellar medium of galaxies and the early Universe. Here we perform the first quantitative comparison of theoretical models of the dynamo growth rate and saturation level with three-dimensional magnetohydrodynamical simulations of supersonic turbulence wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 50 publications
14
135
1
1
Order By: Relevance
“…We seed the simulations with trace initial magnetic fields; these fields are amplified by the turbulent dynamo until they saturate around equipartition (magnetic energy about ∼5% of the kinetic energy, in good agreement with other simulations using a variety of different numerical techniques and analytic estimates; see Schekochihin et al 2004;Brandenburg & Subramanian 2005;Federrath et al 2014). However,because they only indirectly influence the dynamics by weakly changing the structure of turbulence, we find that magnetic fields do not significantly change our conclusions compared to hydro-only runs.…”
Section: A3 Initial Conditionssupporting
confidence: 77%
“…We seed the simulations with trace initial magnetic fields; these fields are amplified by the turbulent dynamo until they saturate around equipartition (magnetic energy about ∼5% of the kinetic energy, in good agreement with other simulations using a variety of different numerical techniques and analytic estimates; see Schekochihin et al 2004;Brandenburg & Subramanian 2005;Federrath et al 2014). However,because they only indirectly influence the dynamics by weakly changing the structure of turbulence, we find that magnetic fields do not significantly change our conclusions compared to hydro-only runs.…”
Section: A3 Initial Conditionssupporting
confidence: 77%
“…This corresponds to the exponential growth phase, and is characteristic for the small-scale dynamo [37; 44]. The power spectra converge first on the smallest spatial scales, at which point the dynamo enters the slow growth phase [44]. This may be seen by the time delay for the larger scales of the power spectra to converge.…”
Section: Resultsmentioning
confidence: 99%
“…Turk et al (2012) and Latif et al (2013d) performed cosmological magneto-hydrodynamical simulations and confirmed that the small-scale dynamo is operational during the formation of protogalaxies, and the operation of the smallscale dynamo has been confirmed even for turbulence driven by supernova explosions (Balsara et al 2004;Balsara & Kim 2005). Furthermore, substantial progress has been made in the theoretical understanding of the dynamo, including the regime at high Mach numbers, different types of turbulence, and a large range of magnetic Prandtl numbers (Federrath et al 2011a(Federrath et al , 2014Schober et al 2012b;Bovino et al 2013;Schleicher et al 2013a).…”
Section: Introductionmentioning
confidence: 88%